Overview of adherence and factors related to medication adherence in hypertensive patients at Puskesmas Tembuku 1 in 2017 - Thivyaroobini Ramah; Komang Ayu Kartika Sari (Intisari Sains Medis, 2018)
Background: Hypertension remains a public health issue in Indonesia as its prevalence increases considerably. Adherence to treatment is an important factor in the long-term health and well-being of hypertensive patients. Basic Health Research (Riskesdas) in 2007 reported that the prevalence of hypertension in the population aged over 18 years in Indonesia is as high as 31.7%, of which only 7.2% known that they had hypertension and only 0.4% took antihypertensive medications. Coverage of hypertension cases at Puskesmas Tembuku I in 2016 increased by 50% from the previous year, from 292 cases to 584 cases.Methods: The research was conducted in the coverage area of Tembuku I Community Health Center, Bangli Regency, in 2017. The descriptive cross-sectional method was used in this research. 81 respondents were chosen as research sample using non-probability consecutive sampling method. Primary data were collected through interviews on the research sample using questionnaire and Morisky Medication Adherence Scale (MMAS-8).Results: Most of the respondents had low medication adherence (96.3%), followed by moderate adherence (3.7%). None of the respondents had high medication adherence. Most of the respondents had low knowledge of hypertension (70.4%) and had sufficient access to healthcare facilities (71.6%). Most of the respondents reported high family support (93.8%), and high support from healthcare officials (71.6%). Most of the respondents (97.5%) reported high motivation.Conclusion: Low medication adherence and low knowledge regarding hypertension were observed, despite sufficient access to healthcare facilities, high family and healthcare officials support, and high motivation in hypertensive patients.